2008
DOI: 10.1055/s-2008-1038671
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyperbaric Oxygen Therapy on Wound Healing After Tracheal Resection and End-to-End Anastomoses in Rats: Results of Early Observations

Abstract: Our short-term observation results demonstrate that HBO treatment increases tracheal healing and decreases the complication ratios. HBO may be preferred as a supportive treatment modality during the healing period after tracheal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Experimental data have shown hyperbaric oxygen improves anastomotic integrity in animal models 386 387. Recently, 72 patients who underwent elective open infraperitoneal anastomosis for rectal cancer were randomised to 30% or 80% oxygen at induction and for 6 hours postoperatively 388.…”
Section: Section 8: Emergency Oxygen Use In Hospital Settingsmentioning
confidence: 99%
“…Experimental data have shown hyperbaric oxygen improves anastomotic integrity in animal models 386 387. Recently, 72 patients who underwent elective open infraperitoneal anastomosis for rectal cancer were randomised to 30% or 80% oxygen at induction and for 6 hours postoperatively 388.…”
Section: Section 8: Emergency Oxygen Use In Hospital Settingsmentioning
confidence: 99%
“…In large airway ischemia models in mice, HBOT has been shown to promote anastomotic healing, and is known to improve oxygen delivery and wound healing by inducing angiogenesis and neovascularization, recruiting endothelial stem cells, and reducing inflammation . Recent reports have also indicated that HBOT can be safely administered to patients with postoperative airway compromise.…”
Section: Discussionmentioning
confidence: 99%
“…We also found significant upregulation of hypoxia-inducible genes in donor airways, with expression of VEGFA, KDR, and HMOX1 being associated with prolonged respiratory failure, prolonged hospitalization, extensive airway necrosis, and CAS. 13 In large airway ischemia models in mice, HBOT has been shown to promote anastomotic healing, [30][31][32] and is known to improve oxygen delivery and wound healing by inducing angiogenesis and neovascularization, recruiting endothelial stem cells, and reducing inflammation. [33][34][35][36] Recent reports have also indicated that HBOT can be safely administered to patients with postoperative airway compromise.…”
Section: Discussionmentioning
confidence: 99%
“…In the third step, the rabbits were decompressed at a rate of 0.15 ATA/min as described elsewhere. [9,10] …”
Section: Hyperbaric Oxygen Treatmentmentioning
confidence: 99%
“…[6][7][8][9][10] In practice, hyperbaric oxygen has also been successfully employed in the treatment of chest wall radionecrosis. [11,12] However, there is insufficient data in the literature regarding cartilage regeneration and growth after the resection of the deformed cartilages on the chest wall.…”
mentioning
confidence: 99%